Destination foodscape : a stage for travelers' food experience - Björk, Peter; Kauppinen-Räisänen, Hannele (Elsevier, 2019)
This study elaborates on the foodscape construct and explores it within tourism. The study contributes to the literature by introducing destination foodscape and presenting a novel framework for understanding a destination's food environment. The typology of foodscapes shows how the destination foodscape construct is multifarious. Destination foodscape is influenced by well-defined and organized service environments but goes beyond staged service encounters to non-organized environments. Regarding the implications for destination and tourism management, this study suggests placing a stronger emphasis on local food as a marketing dimension, involving local people by making them aware of their role in the destination foodscape and their importance for travelers' food experiences as part-time marketers, as well as in creating public-private destination spaces where tourists can have more private food experiences.
Keywords: destination foodscape; food; foodscape; experience; servicescape; qualitative study; food; marketing; tourism; food habits; eating arrangement; experiences (knowledge); tourist services; consumer behaviour; food tourism; food culture; fi=Markkinointi|en=Marketing|